I'm feeling lucky : the confessions of Google employee number 59 - Edwards, Douglas, 1958- (Boston : Houghton Mifflin Harcourt, 2011)
Comparing Google to an ordinary business is like comparing a rocket to an Edsel. Edwards, Employee Number 59, offers the first inside view of Google, giving readers a chance to fully experience the bizarre mix of camaraderie and competition at this phenomenal company. Edwards, Google's first director of marketing and brand management, describes it as it happened. We see the first, pioneering steps of Larry Page and Sergey Brin, the company's young, idiosyncratic partners; the evolution of the company's famously nonhierarchical structure (where every employee finds a problem to tackle or a feature to create and works independently); the development of brand identity; the races to develop and implement each new feature; and the many ideas that never came to pass.
You Are One of Us. -- From whence I came -- In the beginning -- A world without form -- Marketing without "marketing" -- Giving process its due -- Real integrity and thoughts about God -- A healthy appetite for insecurity -- Cheap bastards who can't take a joke -- Wang dang doodle, good enough is good enough -- Rugged individualists with a taste for porn -- Google Grows and Finds its Voice. -- Lift off -- Fun and names -- Not the usual yada yada -- Googlebombs and mail fail -- Managers in hot tubs and in hot water -- Is New York alive? -- Where We Stand. -- Two speakers, one voice -- Mail enhancement and speaking in tongues -- The sell of a new machine -- Where we stand -- Aloha AOL -- We need another billion-dollar idea -- Froogle and friction -- Don't let marketing drive -- Mistakes were made -- Can This Really be the End? -- S-1 for the money -- Timeline of Google events.
Includes bibliographical references and index.
Keywords: Google (Firm) -- History; Internet industry -- United States -- History; Web search engines; Corporate culture -- United States -- History; Marketing -- United States -- History